The Duyfken: An Exploration of the Roles of a Replica Ship - Worth, Howard (Australian Association for Maritime History, 2013)
On 11 January 2012, in a press release headed '''Little Dove''' to return home to WA', Western Australia's Deputy Premier and Minister for Tourism, Kim Hames, announced that the Duyfken 1606 Replica Foundation would receive government support to bring the Duyfken replica back to the state. The release went on to say that the support would take the form of a $263,000 grant for the Duyfken to sail from Sydney to Perth, with an additional $125,000 per annum (indexed) for 10 years for it to be home ported in Perth. Two state government staff members would also be provided to assist with managing the project. Dr Hames said the funding would provide the Duyfken with a permanent home, while also creating a new tourism attraction and educational experience for West Australians and visitors.